Analysis of the effect of bus stops on the bus speed regarding the usage of public bus fleet as probe vehicles - Llorens Ponsoda, Ignacio (2021)
Dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Geospatial Technologies